2015
DOI: 10.1142/s0129065715500185
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Combined with EEG Reveals Covert States of Elevated Excitability in the Human Epileptic Brain

Abstract: In GGE, the interictal period contains multiple, quasi-stable covert states of excitability a class of which is associated with the generation of TMS-induced EDs. The relevance of these findings to theoretical models of ictogenesis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 69 publications
1
14
0
2
Order By: Relevance
“…The combined use of TMS and EEG has shown great promise in studies of the brain in health and in disease by informing us about cortical excitability, connectivity, and dynamic state [2,12,13,[35][36][37][38]. However, artifacts, especially those from scalp muscles, have limited the use of this technique to areas of the head with no musculature or to latencies where muscle artifacts no longer disturb the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined use of TMS and EEG has shown great promise in studies of the brain in health and in disease by informing us about cortical excitability, connectivity, and dynamic state [2,12,13,[35][36][37][38]. However, artifacts, especially those from scalp muscles, have limited the use of this technique to areas of the head with no musculature or to latencies where muscle artifacts no longer disturb the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Futhermore, it found that connectivity is drastically weakened in lowered states of consciousness such as deep sleep [5] or coma [11][12]. More recently, progress has been made in developing TMS-EEG for diagnostic purposes, in particular in the case of epilepsy [13]. However, we are still in many cases limited to stimulating areas away from cranial muscles or to studying responses at latencies when the TMS-evoked muscle activity has ceased.…”
Section: Tms-eegmentioning
confidence: 99%
“…Furthermore, several groups have identified EEG correlates of the paired-pulse TMS-EMG metrics that are abnormal in patients with epilepsy 20,21 . Of particular relevance, previous studies have also suggested that abnormal stimulation-evoked EEG activity is seen in patients with epilepsy 22-25 .…”
Section: Introductionmentioning
confidence: 92%
“…We suggest that relaxing the pre-ictal state detection problem to a pro-ictal (high seizure susceptibility) state detection problem might prove crucial, followed by a biological and theoretical characterization of such pro-ictal states. Some experimental (Badawy et al, 2009;Kimiskidis et al, 2015) and theoretical evidence already exists, on which future work can build. Furthermore methods of deriving model parameters from data have been developed (Freestone et al, 2011;Ullah and Schiff, 2009), enabling the possibility of model-based design of patient-specific closed-loop stimulation protocols for the pro-ictal state.…”
Section: Figurementioning
confidence: 99%